آراء الإمام الشافعي فى ذم علم الكلام: نظرة موضوعية في ضوء عقيدة أهل السنة والجماعة - Abdulmuthalif, A.; Mokhtar, A.B.; Mokhtar, A.N. (Universiti Sains Islam Malaysia, 2024)
The discipline of Ilm al Kalam has become a matter of dispute since its beginning. This led the Islamic scholars to take either positive side in supporting and defending it or negative side in criticizing and condemning it. This research paper attempts to understand Imam Shafie’s stand with regard to Ilm al kalam. The research paper starts with an introduction and three chapters. Introduction illustrates the concept of Ilm al kalam and its connection to the Islamic creed. The first chapter discusses the issues related to Islamic creed and our great ancestors’ views and opinions in this regard before Imam Al Shafie. The second chapter concentrates on Imam Shafie’s attitudes towards Ilm al Kalam to clearly define which Ilm al kalam was meant by Imam al Shafie through his views on it and to know definitely whether He praised this discipline or condemned it. The third chapter solely concentrates on exempting Asharie Imams and Scholars from the negative Ilm al Kalam which was condemned by the great ancestors. In order to attain its objectives and the aimed target, this research adopts both descriptive and critical methods. Through this research paper, it is clearly understood that the direct condemnation of Imam al Shafie goes to the Greek philosophy in the metaphysical issues and to all the thoughts and schools which were influenced by Greek philosophy against the holy Quran and prophetic Sunnah. His strong opposition to those sects and his strong support to the theological views of Ahl as Sunnah wa al Jama’ah are based on Al Quran and authentic Sunnah and understood by the pure reason supported by the light of Allah almighty.